Higher-risk breast cancer in women aged 80 and older: Exploring the effect of treatment on survival. (October 2021) - Al-Rashdan, Abdulla; Xu, Yuan; Quan, May Lynn; Cao, Jeffrey Q.; Cheung, Winson; Bouchard-Fortier, Antoine; Kong, Shiying; Barbera, Lisa
Abstract: Background: To understand the association between various treatments and survival for older women with higher-risk breast cancer when controlling for patient and tumor factors. Materials and methods: We conducted a retrospective, population-based study. Women aged 80 years or older and diagnosed between 2004 and 2017 with non-metastatic, higher-risk breast cancer were identified form the provincial cancer registry in Alberta, Canada. Higher-risk was defined as any of following: T3/4, node positive, human epidermal factor receptor-2 (Her2) positive or triple negative disease. Treatments were surgery, radiotherapy and systemic therapy (hormonal therapy, and/or chemotherapy and/or trastuzumab) or a combination of the previous. Cox regression models were used to examine the association between treatments and breast cancer specific survival (BCSS) and overall survival (OS). Results: 1369 patients were included. The median age was 84 years. 332 (24%) of women had T3-T4 tumors, 792 (58%) had nodal involvement, 130 (10%) had Her2 positive tumors, 124 (9%) had triple negative tumors. After a median follow-up of 35 months, 29.5% of patients died of breast cancer whereas 34.2% died from other causes. Patients had a lower adjusted hazard for BCSS if they had surgery (hazard ratio [HR] = 0.37 95% confidence interval [CI]: 0.27, 0.51), or systemic therapy (HR = 0.75, 95%CI: 0.58, 0.98). Patients had an increased probability of breast cancer death in the first 5 years after diagnosis compared to death from other causes. Conclusions: Surgery and systemic therapy were associated with longer BCSS and OS. This suggests that maximizing treatments might benefit higher-risk patients. Highlights: Breast cancer patients aged 80 or older are rarely represented in clinical trials. Association between survival and treatment is unknown for higher-risk patients. Breast cancer death affected around one-third of the higher-risk population. Surgery and systemic therapy were associated with lower breast cancer death.